Ethical issues in videorecording patients lacking capacity to consent - Carlo Petrini (Istituto Superiore di Sanità, 2011)
Videorecording of patients requires the utmost respect for the privacy and confidentiality of the patients. Consent should be requested from patients for all videorecording. When a mental disability or mental or physical illness prevents patients from giving their permission, agreement to recording from a legal representative or from a close relative or carer are necessary. Three documents on this subject issued in the United Kingdom, the United State of America and Italy are briefly summarized and discussed. The problem of consent for videorecording is addressed particularly in reference to persons incapable of making decisions on their own, such as persons in vegetative state. The general ethical framework is outlined and a few practical proposals are given.